Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to show that the given $2$ groups are isomorphic to each other; that is, I want to show that: $$G=\langle x,y\mid x^4=1,x^2=y^2,y^{-1}xy=x^{-1}\rangle$$ is isomorphic to the quaternion group $Q$. In fact the first one is another representation of $Q$ so somehow it's obvious.

However, I want to strictly show it by creating an isomorphism from $G \to Q$ concretely but what is this mapping? Should this mapping send a generator of $G$ (i.e. $ x,y$) to $i,j$ in $Q$? Should I use other methods (for example isomorphism theorems) to prove it?

share|improve this question
1  
Yes, if you send $x$ to $i$ and $y$ to $j$, then you can work out the images of all of the other elements of $G$. You need to check that the images of the relations in $G$are satisfied by their images in $Q$. So you would need to check that $i^4=1$, $i^2=j^2$ and $j^{-1}ij=i^{-1}$. –  Derek Holt Jun 9 '13 at 9:59

3 Answers 3

To complement what Derek Holt has written in his comment, once you have shown that $i, j$ satisfy the relations for $x$ and $y$, you now know that $Q$ is a homomorphic image of $G$.

Now you show that $G$ has at most $8$ elements, from which it follows that $G$ and $Q$ are isomorphic.

To show that $G$ has at most $8$ elements, note that every element can be written as $y^{b} x^{a}$, with $0 \le a < 4$, and $y \in \{ 0, 1 \}$. In fact if you have any product of $x$ and $y$, you can move the $y$ to the left using $$ x y = y x^{-1}. $$ Then note that $x^4 = 1$ and $y^{2} = x^{2}$ ensure that you do not need powers of $x$ other than $1, x, x^{2}, x^{3}$, and powers of $y$ other than $1, y$.

share|improve this answer

You're on the right track, yes. Set $H = \langle x, y \rangle$ (the free group on two generators $x$ and $y$), then $G = H/N$, where $N = (x^4, x^2y^{-2}, xyxy^{-1})$. Now set $f : H \to Q$ such that $f(x) = i$ and $f(y) = j$. This $f$ exists by the universal property of free groups. Since $i,j$ generate $Q$, $f$ is surjective.

The only thing left is computing $\mathrm{ker}(f)$; we actually want to prove that it's equal to $N$.

  • $f(x^4) = i^4 = 1$, $f(x^2y^{-2}) = i^2(-j)^2 = (-1)^2 = 1$, and $f(xyxy^{-1}) = -ijij = -k^2 = 1$, so $N \subset \mathrm{ker}(f)$.
  • I'll leave you as an exercise that $\mathrm{ker}(f) \subset N$ (it's the most tedious part).

So by general theorems, $N \subset \mathrm{ker}(f) \Rightarrow f$ induces a morphism $\bar f : H/N = G \to Q$, and $\mathrm{ker}(f) \subset N \Rightarrow \bar f$ is injective. Since $f$ was surjective, so is $\bar f$, and so $f$ is an isomorphism.

This method is a good general method to work with group presentations. Send the generators somewhere, and verify that the relations are still satisfied. The most difficult and tedious part is the last one: verifying that you don't introduce new relations (ie. $\mathrm{ker}(f) \subset N$).

share|improve this answer

The two presentations are

$$ G = \langle x, y \;|\; xxxx = 1, xx = yy, x = yx^{-1}y^{-1} \rangle $$ $$ Q = \langle -1, i, j, k \;|\; (-1)^2 = 1, i^2 = j^2 = k^2 = ijk = -1 \rangle $$

We can try to transform one presentation into the other.

The first relation hints that $-1 = xx (= yy)$ and $i = x$, $j = y$.

Now notice that the $ijk = -1$ relation will allow us to recover $k$ as $k = i^{-1}j^{-1}(-1) = x^{-1}y^{-1}yy = x^{-1}y$.

So introducing the (redundant, hence unchanging) relations $z = xx$ and $w = x^{-1}y$ you can explicitly see how one turns into the other.

I think the other answers are better, but it is kind of fun and a useful skill to be able to work with concrete presentations.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.